Fabrication of a C/C-SiC-TiC-TaC composite by hybrid wet infiltration - Makurunje, Phylis Sarah (My University, 2016)
A novel Cf/C-SiC-TiC-TaC composite was successfully fabricated by performing reactive melt infiltration (RMI) by means of pressureless spark plasma sintering (SPS) at 1700◦C to permeate molten 66.7Si-17.9Ti-15.4Ta alloy into a porous Cf/C composite prepared by polymer impregnation and pyrolysis (PIP). The Cf/C composite preform was of density 1.54g/cm3 and open porosity 21%, obtained after 3 cycles of PIP with resole phenolic resin. An amorphous carbon matrix was thus obtained and was confirmed by X-Ray Diffraction (XRD) and Raman spectroscopy. The 66.7Si-17.9Ti-15.4Ta alloy prepared by arc melting from TaSi2 and TiSi2 powders formed a solid solution of (Ta,Ti)Si2 and (Ta,Ti)5Si3. When the alloy was infiltrated into the Cf/C composite preform cubic face centred carbides of Ta, Ti and Si, and the (Ta,Ti)C solid solution were obtained at 1700°C by SPS for 30 minutes. At 1600°C the UHTC matrix was predominantly unreacted silicides; SiC is the only carbide which was convincingly formed, although (Ta,Ti)C was observed by XRD and SEM to have incipiently precipitated at the C/alloy interface. At 1800°C the carbide formation reactions extended to the reinforcing fibres, thus compromising the fibres’ reliability. 1700°C was deemed the excellent trade-off temperature for the formation of the Cf/C-SiC-TiC-TaC composite, wherein an acceptable compromise of the extent of carbide-forming reactions completion and limiting the damage of the melt to the fibres. Upon exposure to an oxyacetylene flame of at least 3000°C, the Cf/C-SiC-TiC-TaC composite showed thermomechanical degradation first, and thermochemical degradation thereafter. After 7.5s of exposure to the oxyacetylene flame (4 MW/m2 heat flux) placed 19mm away, the unprotected Cf/C composite showed a mass ablation rate of 0.0402g/s and a linear ablation rate of 0.377 mm/s. The UHTC showed a low mass ablation rate of 0.00388 g/s and a low linear ablation rate of 0.00216 mm/s owing to the scale of the oxides formed adhering to the surface of the composite. The scale, analysed by scanning electron microscopy, X-ray diffraction, electron dispersive spectroscopy and electron probe micro-analysis, showed that the composite constituents had the ability to form glassy self-healing eutectics based on SiO2 (Ta5O2-SiO2 and TaTiO4-SiO2). The Cf/C-SiC-TiC-TaC composite is a promising candidate for the sharp nose and leading edges of hypersonic vehicles.
Submitted in fulfilment of the requirements for the degree of Master of Science in Engineering Materials and Metallurgical Engineering University of the Witwatersrand Johannesburg, South Africa 2015